Bases, processes, results and contexts of interorganizational learning in cooperation networks: A multiple case study - Borelli, Verena Alice; Larentis, Fabiano; Wegner, Douglas (REGEPE Entrepreneurship and Small Business Journal, 2021)
Objective: To analyze the constitution of bases, processes, outcomes and contexts of interorganizational learning in cooperation networks. Method: Multiple case study through interviews and document analysis was performed in three cooperation networks, with a predominance of micro and small companies in the industry, commerce and services segments. Main results: Interorganizational learning can be identified on an interorganizational basis, by strengthening the network companies’ competitiveness, providing opportunities for joint participation in activities. Learning processes – formal and informal – have occurred through the exchange of experiences and knowledge sharing. As outcomes, aspects learned in the network have been used internally by companies, which involves their paths and expectations. Theoretical / methodological contributions: We have highlighted the constitution of interorganizational learning, that is, bases, processes and outcomes, as well as their interactions with the context. Relevance / originality: The study contributes to the knowledge in interorganizational learning, especially in its processes, by taking in consideration the importance of multilevel analysis. It expands the scarce number of studies that investigate learning in cooperation networks. Social / managerial contributions: The importance of learning and knowledge generated from interorganizational relationships, with an emphasis on the role of the boundary spanners and on contextual aspects in order to promote qualification of internal processes and to expand the comprehension of costs and risks involved. JEL CODE: L26, L29, M10, M19 <!– Start Crossmark Snippet v2.0 –><!– End Crossmark Snippet –>